2017
DOI: 10.1155/2017/4820414
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Ameliorates Liver Injury Induced by Chronic plus Binge Ethanol Feeding by Modulating Oxidative Stress and Inflammation via CYP2E1 and NRF2 in Mice

Abstract: Alcoholic liver injury leads to serious complication including death. The potential role of baicalin at the transcription level in mice model of alcohol injury is not known yet. In this study, we examined the effect of baicalin against chronic plus binge ethanol model in mice and understanding the mechanism of protection. Liver function, histology, steatosis, inflammation, NF-κB activity, oxidative stress sources, nuclear translocation of NRF2 transcription factor, and cell death were assessed. Treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Curcumin to exert a protective effect. Additionally, He et al (2017) reported that Baicalin could increase Nrf2 nuclear translocation and promote its target genes HO-1 and NQO1 expression in chronic and binge ethanol-fed mice. Our present study showed that the combined treatment with Curcumin and Baicalin further up-regulated the mRNA and protein levels of Nrf2, HO-1 and NQO1 in rat liver, and the protective effect of combined two drugs was better than that of the single drug.…”
Section: Discussionsmentioning
confidence: 99%
“…Curcumin to exert a protective effect. Additionally, He et al (2017) reported that Baicalin could increase Nrf2 nuclear translocation and promote its target genes HO-1 and NQO1 expression in chronic and binge ethanol-fed mice. Our present study showed that the combined treatment with Curcumin and Baicalin further up-regulated the mRNA and protein levels of Nrf2, HO-1 and NQO1 in rat liver, and the protective effect of combined two drugs was better than that of the single drug.…”
Section: Discussionsmentioning
confidence: 99%
“…Therefore, the inhibition of metabolic activation of CYP2E1 and oxidative stress, to promote the antioxidant defense system, can confer protection against hepatotoxicity induced by long‐term MTX intervention. It has been reported that the nuclear factor erythroid 2‐related factor 2 (Nrf2) plays a key role in the adaptive response against increased oxidative stress caused by CYP2E1 in the rat liver (He et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…AACS, as a lipid metabolism factor, helps to synthesize fatty acids and cholesterol, highly related with fat metabolism dysfunction [44]. Fat metabolism dysfunction is considered to be the progression of alcoholic fatty liver, which can further induce oxidative stress and inflammatory response [6,45]. AM effectively modulates the levels of AACS and reduces the numbers of lipid droplets in the liver, suggesting its inhibition on fat metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive drinking can cause alcoholic fatty liver within 2 or 3 weeks and may have further effects on the immune system [3]. Alcohol consumption is also highly correlated with the progression of alcoholic fatty liver [4], causes liver damage, and helps to enhance the production of proinflammatory cytokines and chemokines [5,6], which can enhance the concentration of macrophages and neutrophils for promoting the inflammation response [7]. Long-termed alcohol consumption causes dysfunction within the mitochondrial electron transport chain, resulting in the overgeneration of ROS [8,9].…”
Section: Introductionmentioning
confidence: 99%